2019
DOI: 10.1111/issr.12194
|View full text |Cite
|
Sign up to set email alerts
|

The effects on intra‐generational inequality of introducing a funded pension scheme: A microsimulation analysis for Estonia

Abstract: This article uses a single male cohort microsimulation model to analyse the intra-generational and distributional effects of a shift in Estonia from a defined benefit pay-as-you-go (PAYG) pension system to a multi-pillared system with a PAYG scheme with contribution-based insurance components and a funded pension scheme. We contribute to the literature on microsimulation by showing how introducing contribution-based insurance components and compulsory defined contribution (DC) schemes can increase pension ineq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The calculated Spearman correlation coefficients showed that the higher gender gap in pension income corresponds to the higher share of people covered by occupational pensions (for the total gap in mean and gap on the 90th percentile the correlations are significant). Generally, this supports the idea that the introduction of mandatory second pillar contributions leads to higher inequality in the retirement income (Piirits and Võrk 2019), tightening the link between labour income and pensions especially at the top of the distribution, among high pension income recipients.…”
Section: Correlations Between Occupational Pension Coverage 65+ and Gsupporting
confidence: 79%
“…The calculated Spearman correlation coefficients showed that the higher gender gap in pension income corresponds to the higher share of people covered by occupational pensions (for the total gap in mean and gap on the 90th percentile the correlations are significant). Generally, this supports the idea that the introduction of mandatory second pillar contributions leads to higher inequality in the retirement income (Piirits and Võrk 2019), tightening the link between labour income and pensions especially at the top of the distribution, among high pension income recipients.…”
Section: Correlations Between Occupational Pension Coverage 65+ and Gsupporting
confidence: 79%
“…Private pensions deepened existing labour market inequalities in industrialized countries by leading to uneven coverage and inequality in pension benefits, in particular, for older pensioners, single pensioners, women and ethnic minorities (Behrendt, 2000; Sunley, 2000). Rising inequality and old‐age poverty effect is also found by Zaidi, Grech, and Fuchs (2006), Been, Caminada, Goudswaard, and van Vliet (2017) and Piirits and Võrk (2019) in the EU. Similarly, the shift to a mixed pension model from 1991 to 2015 in China generated pension inequality and wider social stratification by privileging the better‐off (Zhu & Walker, 2018).…”
Section: Private Pensions and Inequality: Findings In The Literaturesupporting
confidence: 56%
“…The potential distributional effect of pension systems has been the subject of empirical evaluations in several countries. Findings from previous studies agree that shifts from a defined-benefit system towards a quasi-actuarial defined-contribution scheme would reduce intragenerational redistribution, hence increasing the levels of inequality among retirees (Fasang 2012;Lindbeck and Persson 2003;Piirits and Võrk 2019;Tyrowicz et al 2018). Fortunately, this is not associated with higher consumption inequality.…”
Section: Social Protectionmentioning
confidence: 77%